Spatial Information on the Establishment of Small Pelagic Fish Potentials in the Tapanuli Tengah and Sibolga Waters - Rosmasita, Rosmasita; Silalahi, Bastian Putrayadi; Ariani, Fitri; Situmeang, Hensamuel; Novita, Berliana (Jurnal Perikanan dan Kelautan, 2020)
Tapanuli Tengah and Sibolga are one of the producers of small pelagic fish in the waters of West Sumatera. Spatial information on estimating the potential of small pelagic fish in the waters of Central Tapanuli and Sibolga is needed to determine the sustainability of the fish and make it easier for fishermen to catch fish. This research was conducted in February-April 2020 by utilizing secondary data from the North Sumatra Province Fisheries and Maritime Service in 2010 - 2015 in the preparation of the Coastal and Small Islands Zoning Plan (RZWP3) in 2016. The result showed the potential of small pelagic fish that exist in Tapanuli Tengah and Sibolga waters there are 18 species with a total volume and value of production, namely: Sibolga is 23,699.2 Tons (Rp.382.45 Billion) and Tapanuli Tengah is 16,921.8 Tons (Rp. 254.37 Billion). Estimation of fish abundance in Tapanuli Tengah and Sibolga waters are classified in Medium and High. The types of fish in Tapanuli Tengah waters are: Restrelinger spp, Selaroides leptolepis, stolephorus commersonii and Mugil Sp. Whereas in Sibolga waters the types of fish that are classified as having high abundance are Stolephorus commersonii, Decapterus ruselli and Dussumieria spp, while Restrelinger spp and Selaroides leptolepis classified is medium.